2014
DOI: 10.1007/s00414-014-0981-5
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics of 17 Y-chromosomal STRs loci in Garo and Santal tribal populations in Bangladesh

Abstract: Allele frequencies and haplotype diversity of 17 Y-chromosomal short tandem repeat (STR) loci included in Y-filer™ PCR amplification kit were studied in 120 Garo and 139 Santal male individuals residing in two distinct regions of Bangladesh. A total of 99 different haplotypes from Garo and 129 different haplotypes from Santal individuals were observed with a corresponding discrimination capacity (DC) of 0.825 and 0.928, respectively. A comparison of the studied data with the published data from Y-STR haplotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Nei's genetic distances between Santal population and 28 other published populations.The analysis showed that the Santals lie genetically close to the Munda population belonging to a cluster which includes Kora, Lodha, Karmali, Maheli, Gond, Bhil, Tamil, and Mahadev Koli from different states of India (Fig1). Neighbor-joining tree bases on Nei's DA distance among Santals and 28 other geographically close populations.A previous study conducted from this laboratory based on Ychromosomal STRs also revealed a close genetic relationship between Santal population from Dinajpur, Bangladesh and Munda population from Jharkhand, India25 . The genetic affinity of Santal population with these populations may be due to a possible sharing of paternal lineage and genes during migration.In conclusion, this study demonstrated that the 15 autosomal STR loci reported here offer a highly discriminating system for use in parentage testing and forensic identification of individuals in this population.…”
supporting
confidence: 61%
“…Nei's genetic distances between Santal population and 28 other published populations.The analysis showed that the Santals lie genetically close to the Munda population belonging to a cluster which includes Kora, Lodha, Karmali, Maheli, Gond, Bhil, Tamil, and Mahadev Koli from different states of India (Fig1). Neighbor-joining tree bases on Nei's DA distance among Santals and 28 other geographically close populations.A previous study conducted from this laboratory based on Ychromosomal STRs also revealed a close genetic relationship between Santal population from Dinajpur, Bangladesh and Munda population from Jharkhand, India25 . The genetic affinity of Santal population with these populations may be due to a possible sharing of paternal lineage and genes during migration.In conclusion, this study demonstrated that the 15 autosomal STR loci reported here offer a highly discriminating system for use in parentage testing and forensic identification of individuals in this population.…”
supporting
confidence: 61%
“…Thus, there is a critical need for further research considering the unique family structures and socio-cultural contexts of various underprivileged indigenous women groups residing in Bangladesh's lowlands. To fill this research gap, the current study focused on the case of the Garo indigenous women lived in the lowlands of Mymensingh, Netrakona, Gazipur, Sherpur, and Tangail [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other indigenous groups of this country, the Garo belongs to a matrilineal-matrilocal society [ 47 ] and represents one of the few close-knit indigenous communities in the world [ 48 ]. Being significantly impacted by neighborhood culture and practices, the Garo indigenous population maintains different sociocultural traditions different from other indigenous communities and mainstream Bangladeshis [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study examines how racism impacts Garo Indigenous women’s experience of accessing biomedical maternal healthcare in Bangladesh. The Garo community is one of the largest Indigenous communities in Bangladesh [ 46 ], and one of the few close-knit communities worldwide [ 47 ]. They follow a unique ‘matrilineal-matrilocal’ family structure [ 47 ].…”
Section: Introductionmentioning
confidence: 99%